(untitled) (Nepalese Journal of Development and Rural Studies, 2019)
The study seeks to explain role of Rural Development Bank (RDB) for empowering women from poverty alleviation perspective. More so, this study was conducted in Shankarnagar located in Rupendehi District. Under quantitative case study methodology, necessary data are collected from 120 respondents selected randomly. The results show that Shankarnagar area office of RDB has played remarkable role in reducing poverty in the study area. The social and financial programmes implemented this bank has helped to alleviate poverty in some extent. It has also contributed to increase family income, self employment opportunities, better health and hygiene, better living standard, saving and credit activities and access to quality child education. Hence, better to make further social/financial plans/programmes for reducing poverty in general and empowering women in particular.